Negative emotions and creativity among Chinese college students during the COVID-19 pandemic: the mediating role of psychological resilience and the moderating role of posttraumatic growth - Wei Zeng; Dongtao Huang; Qian Li; Yanhua Xu; Ziying Xu; Chujin Wu; Zhihao Chen; Yuhao Yang; Jinlian Shao; Xingrou Wu; Ziqi Zhu; Jiamin Wu; et al. (BMC, 2022)
Abstract Background The aim of the study was to use a moderated mediation model to understand and examine the relationship between negative emotions and creativity among college students during the COVID-19 pandemic, using psychological resilience as a mediator and posttraumatic growth as a moderator. Methods A sample of 881 college students in mainland China completed a self-report questionnaire that included four scales: the Depression-Anxiety-Stress Scale, Psychological Resilience Scale, Runco Ideational Behavior Scale and Posttraumatic Growth Inventory. Results Findings indicated that:(1) negative emotions were a strong predictor of creativity; (2) psychological resilience partially mediated the association between negative emotions and creativity; and (3) posttraumatic growth moderated the positive effect of psychological resilience, such that the indirect effect between negative emotions and creativity via psychological resilience was stronger for someone with a low level of resilience. Conclusion The findings further clarify the mechanisms that affect the relationship between negative emotions and creativity among college students.